Test-Anxiety and Coping-Strategies as Predictors of Psychological-Wellbeing of Students with Disabilities in Inclusive Basic Schools in Lagos State, Nigeria - Akinsemoyin, Omoshalewa L.; Olawuyi, Bolanle O. (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Kupang, 2025)
Inclusive education aims to provide equal access to quality basic education by meeting diverse learners' needs. Tests, integral to academic assessment, can trigger anxiety in students, impacting their psychological-wellbeing. Students (with disabilities) with better coping strategies may handle testing situations more effectively, influencing their psychological-wellbeing. This study examined test anxiety, coping strategies, and psychological-wellbeing of students with disabilities in inclusive basic schools in Lagos State. The objectives were to assess the levels of test anxiety, coping strategies employed, psychological-wellbeing, and investigate test anxiety and coping strategies as predictors of psychological well-being. A correlational design was employed, with a population of 208 upper basic nine students with disabilities in public inclusive schools. Data was collected from 189 basic nine students with disabilities using validated instruments on test anxiety, coping strategies, and psychological-wellbeing. Findings revealed moderate levels of test anxiety and psychological-wellbeing, with problem-focused and emotion-focused coping strategies commonly used. Test anxiety and coping strategies are not significant predictors of psychological-wellbeing of students with disabilities. The study recommended that, Inclusive schools in Lagos State should organize Parent Teachers Conference on how to support children's psychological-wellbeing by understanding test anxiety and coping strategies.